Growth performance, nutrient digestibility, and ruminal fermentation of dairy calves fed starter diets with alfalfa hay versus corn silage as forage and soybean oil versus palm fatty acids as fat source - Pedram Panahiha; Hamidreza Mirzaei-Alamouti; Mehdi Kazemi-Bonchenari; Jörg R. Aschenbach (Journal of Dairy Science, 2022)
ABSTRACT: The present study was intended to evaluate the effect of forage source (alfalfa hay; ALF vs. corn silage; CS) along with a supplemental fat source (soybean oil; SO vs. rumen-inert palm fatty acids; PF) on growth performance, nutrient digestibility, and ruminal fermentation in dairy calves. Forty-eight new-born Holstein female calves (3 d old) were assigned to one of 4 treatments: (1) alfalfa hay with soybean oil (ALF–SO); (2) alfalfa hay with palm fatty acids (ALF–PF); (3) corn silage with soybean oil (CS–SO); (4) corn silage with palm fatty acids (CS–PF). Starter diets had equal amounts of forage (100 g/kg dry matter; DM) and fat source (30 g/kg DM). Calves were fed a constant amount of milk (d 1 to 63) and had ad libitum access to water and starters (d 1 to 83). The lowest and greatest starter intakes during the preweaning period occurred in ALF–SO and CS–PF, respectively. This coincided with forage × fat source interaction for average daily gain (ADG) during preweaning. The forage source affected total DM intake and ADG over the entire period, body weight (BW) at weaning, and final BW with greater values in calves that received CS compared with ALF. The concentrations of total short-chain fatty acids and butyrate were increased, whereas concentration of acetate and acetate:propionate ratio were decreased in the rumen of calves fed CS compared with ALF. Feeding CS increased urinary excretion of allantoin and, as a trend, total purine derivatives (PD) and estimated microbial protein synthesis in comparison with ALF. The fat source affected starter intake, ADG, and BW postweaning with the highest values in PF. The digestibility of neutral detergent fiber, crude protein and, as a trend, organic matter were higher in calves fed PF compared with SO. Calves fed PF had lower ruminal ammonia-N concentration and urinary N excretion and greater urinary excretion of allantoin and total PD. Calves receiving SO had a lower ruminal protozoa population. In conclusion, supplementing starter diets with CS and PF is superior to ALF and SO. Interaction of the positive effects of CS and PF on performance underlines that concurrent supplementation of CS with PF is especially recommendable in young calves before weaning.